Performance analysis of SFBC‐OFDM system with channel estimation error over generalized fading channels. Issue 3 (20th February 2018) - Singh, Daljeet; Joshi, Hem Dutt
Abstract: In this paper, the performance of space‐frequency block code orthogonal frequency‐division multiplexing (SFBC‐OFDM) system is analyzed over different fading channels using a generalized approach. General closed‐form expressions of average bit error rate (ABER) are derived for SFBC‐OFDM system. Both M‐ary phase‐shift keying and M‐ary quadrature amplitude modulation techniques have been considered in this analysis. The effect of imperfect channel estimation on ABER is included while deriving the ABER expression. The derived expressions are applicable under any given fading conditions provided that the moment‐generating function of fading channel is known. Simulation results are provided to verify the numerical results obtained from the derived expressions. Abstract : In this manuscript, we have done performance analysis of SFBC‐OFDM system over different fading channels using a generalized approach. General closed‐form expressions of average BER for both M‐PSK and M‐QAM have been derived which are valid for any given fading condition with a defined MGF. The effect of Channel estimation error (CSI) is included in ABER analysis. The derived expressions are simple and computationally efficient.